The Impact Of Digital Marketing, Product Quality And Price On Consumer Buying Interest In Luce Coffee Products In Sidoarjo - Millatur rohmah; Misti Hariasih (JURNAL ILMIAH EDUNOMIKA, 2023)
This study aims to find out that Digital Marketing, Product Quality and Price have a significant effect on consumer buying interest. This research uses quantitative methods. Sampling using non-probability sampling technique. There were 96 respondents involved in this study. Data collection uses a questionnaire distributed via google form. As well as processing the data using the SPSS Statistics 25 program. This study obtained the results that Digital Marketing has a significant influence on consumer buying interest, product quality has a significant influence on consumer buying interest, and price has a significant influence on consumer buying interest in Luce Coffee products in Sidoarjo.